Pain Following the Use of Anesthesia Formulation Among Individuals Undergoing Cataract Surgery: A Randomized Controlled Trial - Toro, Mario D.; Nowakowska, Dominika; Brzozowska, Agnieszka; Reibaldi, Michele; Avitabile, Teresio; Bucolo, Claudio; Murabito, Paolo; Chisari, Clara; Nowomiejska, Katarzyna; Rejdak, Robert (Frontiers in Pharmacology, 2020)
Purpose: To assess the pain intensity of two intraocular solutions in patients undergoing cataract surgery and evaluate the factors influencing the patients’ postoperative activities. Methods: Sixty-two patients undergoing cataract surgery were randomized to receive Mydrane or a solution of 1% lidocaine and 0.025% of adrenaline as an intraocular anesthetic. The pain intensity was assessed by Visual Analog Scale for Pain (VAS Pain) and Brief Pain Inventory-short form (BPI) on the next day after the surgery. Results: The mean pain score measured preoperatively with VAS Pain was 0.34 in Mydrane group and 0.09 in the reference group (p=0.51). There were no statistically significant differences between the two anesthetic methods with respect to pain intensity during the surgery (p=0.94) and the influence of pain during the last 24 h on activity (p=0.79), mood (p=0.31), social contacts (p=0.29), sleep (p=0.5) and the joy of life (p=0.39). Additionally, there was no statistically significant influence of age, sex, lateralization, co-existing ophthalmological diseases (p=0.98) and post-operative complications (p=0.4) on the experienced pain measured during the surgery and in the last 24 h. Conclusions: Intraocular anesthesia during the cataract surgery using Mydrane seems to be as effective as the solution of 1% lidocaine with 0.025% adrenaline.